Evaluación de diferentes porcentajes de harinas de chía (Salvia hispánica) en la elaboración de mortadela. - Armijos Maldonado, Cristhian Leodan (2016)
The food industry must be in line with new trends food of the clients, and y this way to satisfy their tastes and preferences, offering new nourishing, healthy and innovative products. The cooked meat products provide poor contribution of dietary fiber this product has laxative effects and prebiotics that stimulate digestion and intestinal transit, the main objective of the study is to evaluate the nutritional and economical by replacing different percentages of chia flour in order to make of mortadella. For the improvement of study was developed a completely random design where the characterization of macronutrients that there are in chia seeds and mortadella was done using a proximal analysis “Weende”. getting a contribution on dry basis "chia" of 23, 79% protein, 38.47% crude fiber, 28.96% crude fat, 3.28% carbohydrate and 5.50% ash, thus chia is considered as a complete food and balanced which it is possible to formulate a diet. In order to make the product chia various dosages experienced in the formulation of mortadella, It is the most relevant T3 which adds 5%, determining a contribution of 33.71% protein, 5.27% crude fiber, crude fat 52.59% in 0.02% carbohydrate and 8.41 % ash, the parameter that most significant is the raw fiber as it increases from 0.07 to 5.27% compared to the control. In acceptability test panelists choose mortadella concentration less chia flour because it is less dark than the other treatments, for this reason subsequent recognition where it was proved that can mask the lie turns brown adding 0.5 ml of carmine per kilogram of mass coming to get a view similar to mortadella "piggis" and "The Iberian" staining were performed. This study will offer to the market a mortadella with improved functional properties and nutritional support to help maintain a good state of health in society.